Report on an unannounced inspection of Hydebank Wood Secure College, 9 - 19 May 2016. (2016) - Northern Ireland., Criminal Justice Inspectorate,; Northern Ireland., Department of Education., Education and Training Inspectorate,; Great Britain., Her Majesty's Chief Inspector of Prisons for England and Wales,; Northern Ireland., Regulation and Quality Improvement Authority,
No abstract available